Assessment of Unfermented Beverages Intake by Adult Population in Herat City - Masoumi, Abdullah; Rahimi, Basir Ahmad; Sahel, Nasir Ahmad; Foshanji, Ahmad Shafiq; Shankarappa, T. H. (Food ScienTech Journal, 2023)
Beverages play a prominent role in regulating body activities, such as regulating body temperature, helping to absorb food, protecting tissues, disposal of waste materials, refreshing the body, and increasing body performance. Usually, the human body obtains its required water through the consumption of drinking water, tea, cola, energy drinks, milk and dairy products, coffee and other beverages. We evaluated the amount of beverage intake by the adult population of Herat city during summer 2021. In this research 583 standard questionnaires were randomly distributed among adult population of 15 regions of Herat city and the results were analyzed.  The highest beverage intake was observed for water (2.81±0.92 times/day @ 349.57±190.12 ml for each time) and followed by was tea (1.84±0.89 times/day @ 426.76±228.78 ml each time). The average fluid intake by the adult population was 2390.61 ml per day, where the men drank an average of 2528.91 ml/day and women averaged 2363.88 ml/day of beverages. Most of the participants consumed beverages for the purposes of quenching thirst, health concerns, habitual and refreshment. The findings indicate that the amount of beverage intake by adult population of Herat city is lower than the WHO guidelines and the United States fluid intake recommendations.